Hi there! Have questions about your homework? At Brainly, there are 60 million students who want to help each other learn. Questions are usually answered in less than 10 minutes. Try it for yourself by posting a question! :D

Hi there! Have questions about your homework? At Brainly, there are 60 million students who want to help each other learn. Questions are usually answered in less than 10 minutes. Try it for yourself by posting a question! :D

given --->x-2=0 ===> x=2 now put the above value in given equation........ p{x}= 2x³-2x+k=0 p{2}= 2[2]³-2[2]+k=0 => 2[8]-4=-k => 16-4=-k => 12=-k so, k=-12 plz mark it best

Given that x-2 is factor of 2x^3-2x+k That means when divide 2x^3-2x+k by x-2 we will get the zero in remainder Therefore x-2=0 x=2 Substitue x=2 in 2x^3-2x+k=0 2(2)^3-2(2)+k=0 16-4+k=0 12+k=0 k=-12 Therfore k=-12